Usual presentation of an unusual pathogen – Cryptococcus laurentii meningitis: a case report - Zulfiqar, Azka; Rafia Irfan; Faisal Hanif; Javaid Usman (Journal of the Pakistan Medical Association, 2023)
Infections caused by non-neoformans Cryptococcus spp., including Cryptococcus laurentii, previously thought to be saprophyte and non-pathogenic, have become more common during the past few years, particularly in immunocompromised hosts. To the best of our knowledge here, we present the first case of meningitis in an immunocompromised patient due to a fungus that has never been reported in Pakistan. Our patient, a 40-year old male, who had acquired immunodeficiency syndrome (AIDS) was diagnosed as Cryptococcus laurentti meningitis, with a rare neurological manifestation i.e., cryptococcomas and lepto-meningitis. We presume that exposure to pigeon droppings and acquired immunodeficiency syndrome were the risk factors for this case report. He was treated with liposomal Amphotericin (LAMB) and fluconazole but unfortunately, he rapidly deteriorated and ultimately succumbed to the infection. This case underscores the significance of prompt diagnosis and vigorous treatment of Cryptococcus laurentii meningitis, as well as the need for continued surveillance in immunocompromised individuals.